2020
DOI: 10.3390/toxins12080503
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Abundance and Microcystin Profiles in Two Southern British Lakes: The Importance of Abiotic and Biotic Interactions

Abstract: Freshwater cyanobacteria blooms represent a risk to ecological and human health through induction of anoxia and release of potent toxins; both conditions require water management to mitigate risks. Many cyanobacteria taxa may produce microcystins, a group of toxic cyclic heptapeptides. Understanding the relationships between the abiotic drivers of microcystins and their occurrence would assist in the implementation of targeted, cost-effective solutions to maintain safe drinking and recreational waters. Cyanoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…MCs are hepatotoxic cyclic heptapeptides produced by several bloom-forming cyanobacteria belonging to several genera such as Microcystis , Nostoc , Oscillatoria , Planktothrix and Dolichospermum [ 8 , 9 , 10 , 11 , 12 , 13 ]. Owing to their ring structure, MCs are chemically stable under several field and laboratory conditions with half-life ranging from 0.4 to 22 days [ 14 , 15 , 16 , 17 , 18 , 19 ] and total concentrations varying from less than 1 µg·L −1 to 29,000 µg·L −1 in surface waters [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Dissolved MCs in water bodies are recognized as a major public health hazard and disrupting agents of certain fundamental ecological processes [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCs are hepatotoxic cyclic heptapeptides produced by several bloom-forming cyanobacteria belonging to several genera such as Microcystis , Nostoc , Oscillatoria , Planktothrix and Dolichospermum [ 8 , 9 , 10 , 11 , 12 , 13 ]. Owing to their ring structure, MCs are chemically stable under several field and laboratory conditions with half-life ranging from 0.4 to 22 days [ 14 , 15 , 16 , 17 , 18 , 19 ] and total concentrations varying from less than 1 µg·L −1 to 29,000 µg·L −1 in surface waters [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Dissolved MCs in water bodies are recognized as a major public health hazard and disrupting agents of certain fundamental ecological processes [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microcystins and anatoxin-a have been regularly reported in European waters with concentrations up to 100 and 14.4 µg/L, respectively, during seasonal studies in the recent years (e.g., Italy, Poland, Czech Republic, Germany, Russia, France, and Netherlands [16] and references herein). Many freshwater bodies in the United Kingdom (U.K.) frequently experience cyanobacterial blooms and high microcystin concentrations [17,18]. One study reported that 53% of 117 samples from cyanobacterial blooms reached microcystin concentrations above 0.2 µg/L and 13% of samples exceeded the WHO alert level of 20 µg/L [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to our data, water temperature within the reservoir in a single day showed a positive correlation with MC and CYN concentrations probably due to the spatial and diurnal variation in temperature where warmer areas accumulated more toxins. The DO is considered as a potential indicator for the onset of cyanotoxins derived from lysed cells in a blooming population (Hartnell et al 2020). However, DO of both Mahakanadarawa and Nachchaduwa reservoirs did not show a significant correlation to either MC or CYN.…”
Section: And Cyn Cyanotoxins and Their Spatial Distributionmentioning
confidence: 99%